Current use of specific wearables and factors that would motivate future use of wearables: Results based on the general German adult population - André Hajek; Hans-Helmut König (PLoS ONE, 2026)
Background A conscious use of wearables may be beneficial for health in general. Therefore, we aimed to investigate the current use of specific wearables and factors that would motivate future use of wearables in the German general adult population. Methodology/Principal findings Data were taken from a quota-based online survey which took place in January 2026 (German general adult population, mean age of 47.3 years, 18–74 years, n = 2,591). Individuals were asked about their current use of specific wearables, and non-users were also asked about the factors that would motivate future use of wearables. Slightly more than one in three (34.8%) used one or more wearables. Based on the users, 80.8% used a smartwatch, and 24.3% used a fitness tracker, whereas only a small minority used other wearables (smart ring: 5.4%; smart clothing: 4.1%; smart glasses: 2.0%; hearables: 2.9%). Key factors that would motivate future use of wearables were (in descending order of frequency): need for medical monitoring (e.g., due to future chronic illnesses) (42.0%), lower prices (33.3%), interest in monitoring health (32.9%), health data as an incentive to lead a healthy lifestyle (27.2%), experience technological advances (18.2%), and greater user-friendliness (13.5%). Regressions showed that higher odds of currently using at least one wearable were associated with, among others, being married, living with a dog, leading a healthier lifestyle, and having more chronic conditions. Conclusions/Significance Apart from smartwatches, there is still a lot of potential for growth in user numbers for other wearables. We recommend research in other countries and based on longitudinal data.